Indigenous Dispute Resolution Mechanisms at Haramaya Woreda of Eastern Hararghe Zone, Oromia Regional State, Ethiopia - Tufa Telila, Shambel (IJRDO - Journal of Social Science and Humanities Research, 2017)
The main purpose of this research is to Indigenous Dispute Resolution Mechanisms at Haramaya Woreda of Eastern Hararghe Zone, Oromia Regional State, Ethiopia. Ethiopians especially the people of Oromo who live in Eastern part of the regional state has experienced indeginous conflict resolution mechanism a long period of time. They had been socially and culturally on emphasizing on solving conflicts and looking for family wellbeing which is less recognized by the formal institution of government. Conflict is a naturally and socially occurring phenomenon in day-to- day human interactions and some scholars agreed that conflict is human nature. Conflict may initiated by a single event which can go up into broader and devastating ends. The methodology used in the study is a qualitative one which it enables me to have an understanding of the nature of disputes in the study area and how they are resolved through traditional means. Both Primary and Secondary sources of data were used. Primary data was collected using interview of key informants and elders. This enabled me to gather fundamental information on the nature of disputes and their resolution. Secondary data was gathered from published and unpublished documents and the internet. These secondary sources helped to secure information on historical background of the people in the study area, change and continuity of the socio-political institutions. Informants were interviewed to gain an understanding of the study area and the nature of disputes and the indigenous resolution mechanisms of the community. Furthermore, three elders at Haramaya Woreda who are knowledgeable on the study area, the nature and extent of disputes and how they were resolved were interviewed. The interview took place when one of the group members went to the area during the holidays and stayed for five days. One of the interviewed elders (Aba Amenti) was from the religious institution and the other two were from secular societies serving as elders in the community. The interview took place in Haramaya town at the residence of one of the elders. The interview was conducted in Affan Oromo and it was tape recorded after consent was gained. The researcher also was able to record cases of dispute as recounted by the elders (key informants). These cases were used to look into the process of Jarsuma and its role in reconciling the disputant parties. In the cases pseudonym was used for ethical reasons. Before proceeding with the interview, participants were informed on the nature and purpose of the research, consent was asked and secured.